Implementation Science to Address Health Disparities During the Coronavirus Pandemic (Mary Ann Liebert, 2020)
The coronavirus disease 2019 (COVID-19) pandemic is disproportionally affecting racial and ethnic minorities. In the United States, data show African American, Hispanic, and Native American populations are overrepresented among COVID-19 cases and deaths. As we speed through the discovery and translation of approaches to fight COVID-19, these disparities are likely to increase. Implementation science can help address disparities by guiding the equitable development and deployment of preventive interventions, testing, and, eventually, treatment and vaccines. In this study, we discuss three ways in which implementation science can inform these efforts: (1) quantify and understand disparities; (2) design equitable interventions; and (3) test, refine, and retest interventions.